Pengembangan E-Modul Biologi SMA Berbasis Kearifan Lokal Kopi Jember dan Bermuatan Karakter Islami - Sukmawati, Diva Ayu; Munandar, Kukuh; Priantari, Ika (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
Teaching materials play an important role in supporting the effectiveness of biology learning. Along with the development of digital technology, e-modules have become innovative teaching materials that enable more flexible, independent, and interactive learning. This study aims to determine the level of validity, practicality, and effectiveness of a biology e-module that integrates the local of Jember coffee and contains Islamic characters in the material of biodiversity. This research is development research (Research and Development) using the ADDIE model. The study was conducted from July to November 2025 at SMA Negeri 2 Jember. The trial subjects included six students in the small group and all students of grades X-8 in the large group. The results of the validation showed a validity level of 89% with a very valid category. The results of the practicality test showed a percentage of student responses of 87.11% in the small group and 83.12% in the large group with a very practical category. The effectiveness of the e-module is indicated by the N-gain value of 0.53 in the small group and 0.58 in the large group with a moderate category. Thus, the e-module is declared valid, practical, and quite effective for use as biology teaching material in high school. These findings contribute to the provision of multidimensional teaching materials that align science content with Jember coffee local wisdom and the strengthening of students' Islamic character.